2019
DOI: 10.1177/1461348419854610
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rotor eccentricity on vibration characteristics in a five-stage centrifugal pump with vaned diffusers

Abstract: To determine the effect of rotor eccentricity on the vibration of multistage pumps, a five-stage centrifugal pump with vaned diffusers was selected to experimentally measure the vibration characteristics under both stable condition and unstable condition due to the rotor eccentricity. The results show that the rotor eccentricity results in an irregular orbit of the rotor axis, which is diffused outward. As the flow rate increases, the peak amplitude of the rotor axis' orbit first decreases and then increases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The schematic diagram of the test rig is shown in Figure 2. In this study, the turbomachinery closed-type test rig conforming to IEC-60193 standard 30 is used for the experiment. The data of head, flow rate, shaft power and pressure pulsation were measured.…”
Section: Research Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…The schematic diagram of the test rig is shown in Figure 2. In this study, the turbomachinery closed-type test rig conforming to IEC-60193 standard 30 is used for the experiment. The data of head, flow rate, shaft power and pressure pulsation were measured.…”
Section: Research Objectivementioning
confidence: 99%
“…27,28 Current studies have shown that the gap of vaneless region changes due to eccentricity can affect rotor-stator interaction and the stability of flow. 29,30 Wang et al 31 found that the eccentric impeller has an obvious influences on the muti-stage centrifugal pump caused serious vibration. Zhao et al 32 found that the eccentricity influences radial force and cavitation in reactor coolant pump.…”
Section: Introductionmentioning
confidence: 99%
“…Modal analysis is a crucial basis for analyzing vibration issues in centrifugal pumps and is an essential factor in the design of dynamic devices [ 33 ]. This study focuses on the rotor system of a four-stage centrifugal pump with a balancing disc fixed using a simple beam support.…”
Section: Introductionmentioning
confidence: 99%